The Effect of Empowering Micro, Small and Medium Enterprises on Community Economic Development in Deli Tua District, Deli Serdang District - Nurul Dalimunte (Institute of Computer Science (IOCS), 2022)
The Effect of Empowerment of Micro, Small and Medium Enterprises (MSMEs) on Economic Development in Deli Tua District, Deliserdang Regency (By: Netarius Ndruru) (Supervisors: Dr. Mananda Situmorang, Drs., M.Si and Nurul Dalimunte, S.Sos., M. Si). This study aims to determine how much influence the empowerment of MSMEs has on economic development in Deli Tua District and to determine the extent to which MSME empowerment is carried out in supporting economic development in Deli Tua District. The research method used in this thesis is a quantitative method. The data collection techniques include primary data collection, namely the method of observation, interviews and questionnaires. Then with secondary data collection techniques, namely the library and field studies. To determine the effect of empowering micro, small and medium enterprises on economic development in Deli Tua District, the author uses the product moment correlation coefficient formula. Meanwhile, to test the significant level between the independent variable and the dependent variable, in this case the author uses the t test formula. The results showed that the effect of empowering micro, small and medium enterprises on economic development in Deli Tua District had a strong effect, with a value of r_xy = 0.687. Meanwhile, from the results of the significant level test, it is concluded that there is a positive and significant influence between the empowerment of micro, small and medium enterprises on economic development, with a value of t = 7.389.